Komparasi Pengaruh Langsung dan Tidak Langsung Merek dan Kualitas Produk terhadap Kepercayaan Konsumen dan Loyalitas Pelanggan Produk Tas Elizabeth di Wilayah Kota Jember - Evrylia Tri Purnama Sari; Imam Suroso; Ketut Indraningrat (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aimed to compare the direct and indirect influence between the brand, the quality of product to consumer confidence and customer loyalty in a bag branded products in the Elizabeth City area is categorized as research Jember.Penelitian explanation (explanatory research). The population in this study quantified by means of indicator multiplied by 15 parameters so that the sample n = 7 Ã— 15 = 105, with a purposive sampling bag subscribers Elizabeth City Regional Jember. Data were collected using a questionnaire while the data analysis by SEM. The results of this study showed that the direct influence of brand on customer loyalty by 0.267 while not directly influence brand loyalty of 0.443 customers through customer confidence. Quality direct influence on customer loyalty by 1.022 while not directly influence the quality of the loyalty of 0.049 through trust. The conclusion in that brand and product quality influence on customer trust and customer loyalty Elizabeth bag products in the city of Jember. Companies need to pay attention to the quality of the product to increase the trust and loyalty of customers. Keywords: Quality Product, Brand, Trust, Loyalty